Converting CO2into heterocyclic compounds under accelerated performance through Fe3O4-grafted ionic liquid catalysts - Vishwakarma N.K.; Singh S.; Vishwakarma S.; Sahi A.K.; Patel V.K.; Kant S.; Mahto S.K. (My University, 2025)
Solid supported catalysts such as amines are in high demand for the chemical fixation of CO2 into commodity chemicals. Here, we demonstrate an accelerated platform for 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU)-ionic liquid (IL) catalyzed CO2 fixation via the grafting of DBU-ILs over magnetically separable Fe3O4 nanoparticles (MNPs). The DBU-ILs were covalently immobilized over Fe3O4 MNPs utilizing the thio-ene reaction of allyl-DBU with -SH modified Fe3O4 MNPs. The DBU-IL-grafted Fe3O4 (Fe3O4@DBU-ILs) materials were characterized by Fourier-transform infrared (FT-IR) spectroscopy, field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and vibrating-sample magnetometry (VSM). TEM revealed that the MNPs have a spherical structure with a particle size of 12-20 nm. VSM showed the gradual decrease in magnetization after stepwise grafting from Fe3O4 to Fe3O4@DBU-ILs. The efficacy of the two different Fe3O4@DBU-ILs, Fe3O4@[HDBU+][TFE-] and Fe3O4@[HDBU+][AcO-] prepared by neutralization of Fe3O4@DBU with 2,2,2-trifluoroethanol (TFE) and acetic acid (AcOH), was investigated by simultaneous fixation of CO2 into the important heterocyclic compounds quinazoline-2,4(1H,3H)-dione and benzimidazolone. This approach shows excellent recyclability with a nominal decrease (2-3%) in product yields after each cycle. In particular, the energy-dispersive X-ray spectroscopy (EDX) mapping of Fe3O4@[HDBU+][TFE-] used for five cycles demonstrated significant leaching of TFE. Interestingly, after retreatment with TFE, Fe3O4@[HDBU+][TFE-] showed a similar yield to that of a fresh catalyst. This journal is © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.